2008
DOI: 10.1128/jcm.00230-08
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Laboratory-Developed Test Utilizing Roche Analyte-Specific Reagents for Detection of Staphylococcus aureus , Methicillin-Resistant S. aureus , and Vancomycin-Resistant Enterococcus Species

Abstract: Nasal and perianal swab specimens were tested for detection of Staphylococcus aureus and vancomycinresistant Enterococcus species (VRE) using a laboratory-developed real-time PCR test and microbiological cultures. The real-time PCR and culture results for S. aureus were similar. PCR had adequate sensitivity, but culture was more specific for the detection of VRE.Staphylococcus aureus, especially methicillin-resistant S. aureus (MRSA), and vancomycin-resistant Enterococcus species (VRE) are important pathogens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
1
2
1
Order By: Relevance
“…1ϩ, 1 to 9 colonies; 2ϩ, 1 to 49 colonies; 3ϩ, 5 to 300 colonies; 4ϩ, Ͼ300 colonies. ego, CA) and the Roche LightCycler analyte-specific reagents (ASRs) (15,17,21). Different from Bourdon et al, our findings showed a higher PPV (91%, versus 66.7% in the study by Bourdon et al) after resolution of discrepant results for the vanA gene.…”
Section: Discussioncontrasting
confidence: 57%
“…1ϩ, 1 to 9 colonies; 2ϩ, 1 to 49 colonies; 3ϩ, 5 to 300 colonies; 4ϩ, Ͼ300 colonies. ego, CA) and the Roche LightCycler analyte-specific reagents (ASRs) (15,17,21). Different from Bourdon et al, our findings showed a higher PPV (91%, versus 66.7% in the study by Bourdon et al) after resolution of discrepant results for the vanA gene.…”
Section: Discussioncontrasting
confidence: 57%
“…The mecA PCR results were identical for both the in-house PCR assay and the laboratory-optimized Roche ASR assay, similar to our prior experience (12). Of the 199 specimens tested, 85 (42.7%) were negative and 114 specimens (57.3%) were positive by both assays.…”
Section: Resultssupporting
confidence: 65%
“…Despite this, we have discrepant results between PCR and culture. Studies issuing false-positive results due to vanB suggest that follow-up culture be performed on any vanB-positive results (11,25,26). If the presence of vanB is low in the setting, culture backup may not be warranted.…”
Section: Discussionmentioning
confidence: 99%